Pengaruh Secure Attachment Ibu-Anak terhadap Kemandirian Anak Usia 5-6 Tahun di RA Kelurahan Lagoa Jakarta Utara - Handayani, Oktarina Dwi; Robbi, Anisa Kamila (Universitas PGRI Semarang, 2023)
This research is motivated by the importance of independence in children. Based on initial observations in several RAs in Lagoa Village, North Jakarta, researchers found several independence problems in children including; the child does not want to be left by his mother. When at school, the child cannot store things in their place, and the child cannot complete their activities. The aim of this study was to find out whether there is an effect of mother-child safety attachment on the independence of children aged 5-6 years in RA, Lagoa Village, North Jakarta. This study use a quantitative approach, with a simple linear regression analysis of 0.001 <0.05 which shows that the hypothesis is accepted, namely that there is an effect of secure attachment to the independence of children aged 5-6 years in RA Lagoa, North Jakarta.Keywords: Secure Attachment; Independence; Child